Temi cristologici rilevati nelle Lettere di san Girolamo – pars seconda - Łukaszczyk, Michał (Vox Patrum, 2025)
This article is a continuation of the first part and aims to examine the Christological themes found in Jerome’s Epistles. The monk of Bethlehem deals with Christological themes found in other Church Fathers, but original things appear in his reflections, such as, clarifying the notion of Persona, emphasising the balance and to the same extent the distinction between the humanity and divinity of Christ while clearly emphasising the one subject of both. Furthermore, the discovery of the links between biblical exegesis and Christology and the development of his own original exegetical method should be considered a special achievement of the Monk of Bethlehem. On the basis of the research carried out, it should be concluded that Christological reflection occurs to a significant degree in Jerome’s Epistles.